Pendampingan Unit/Wadah Organisasi Model Pencatatan Transaksi Keuangan dalam Pembukuan Sederhana - Janet Wilsye Litualy; Engrith Grafelia Leunupun; Thimotina Killay; Sitti Fatimah Kamaruddin; Adonia Anita Batkunde; Dwi Kriswantini; Theresia F Sitania (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
The aim of this community service program is to provide assistance and education to the community in Kiera Hamlet, Southwest Maluku Regency regarding recording financial transactions in simple bookkeeping in accordance with applicable financial accounting standards. This program will take place on Saturday 3 to face in Kiera Hamlet, Moa Island, Southwest Maluku Regency. This activity was carried out with the presence of all Kiera hamlet staff, chair of the church congregation council. Church staff, village community and home base lecturers as well as students of the PSDKU Accounting study program, Southwest Maluku Regency. The method used in this activity is a participatory learning method. After carrying out this service, the community will gain knowledge about bookkeeping in managing finances so that the recording process can be carried out regularly.